Stable Epigenetic Variants Selected from an Induced Hypomethylated Fragaria vesca Population - Xu, Jihua; Tanino, Karen K.; Robinson, Stephen J. (Frontiers in Plant Science, 2016)
Epigenetic inheritance was transmitted through selection over generations of extreme early, but not late flowering time phenotypic lines in F. vesca. Epigenetic variation was initially induced using the DNA demethylating reagent 5-azacytidine (5-azaC). It is the first report exploring epigenetic variant selection and phenotypic trait inheritance in strawberry, a model plant species for one of the most important temperate fruit crop families, Rosaceae. Transmission frequency of these traits was determined across generations. Early flowering (EF4) and late stolon (LS) phenotypic traits were successfully transmitted through meiosis across at least five and two generations, respectively. Stable mitotic transmission of the early flowering phenotype was also demonstrated using clonal daughters derived from the 4th Generation (S4) mother plant. In order to further explore the DNA methylation patterns underlying the early flowering trait, the standard MSAP method using isoschizomers Hpa II / Msp I, and a newly modified MSAP method using isoschizomers Tfi I / Pfe I which detected DNA methylation at CG, CHG, CHH sites were used in two early flowering lines, EF4 lines 1 (P2) and EF4 lines 2 (P3), and control lines (P1). A significant reduction in the number of fully-methylated bands was detected in P2 and P3 when compared to P1 using the novel MSAP method. In the standard MSAP, the symmetric CG and CHG methylation was maintained over generations in the early flowering lines based on the clustering in P2 and P3, while the novel MSAP approach revealed the asymmetric CHH methylation pattern was not maintained over generations. This study provides evidence of stable selection of phenotypic traits, particularly the early flowering phenotype through both meiosis and mitosis, which is meaningful to both breeding programs and commercial horticulture. The maintenance in CG and CHG methylation over generations suggests the early flowering phenotype might be related to DNA methylation alterations at the CG or CHG sites. Finally, this work provides a new approach for studying the role of epigenetics on complex quantitative trait improvement in strawberry, as well as providing a tool to expand phenotypic diversity and expedite potential new horticulture cultivar releases through either seed or vegetative propagation.